AL-DAKHIL DALAM TAFSIR ILMI: (Kajian Kritik Husein Al-Dhazabi Atas Kitab Al-Jawahir Fi Tafsir Al-Qur’an) (TAJDID: Jurnal Ilmu Ushuluddin, 2022)
This study discusses Husein al-Dzahabi's criticism of dakhil in the interpretation of Tanthawi Jauhari, which in his interpretation, Tanthawi interprets many verses related to science (al-ayat al-Kauniyah) known by tafsir al-‘ilmi. Using the literature method (library research) and descriptive-qualitative approach, the author describes the data obtained from the book al-Tafsir wa al-Mufassirun and the book al-Jawahir fi Tafsir Al-Qur'an as well as relevant data. So it can be concluded that in his interpretation, Tanthawi takes a considerable portion of the interpretation of al-ayat al-kauniyah (scientific interpretation) and is interpreted briefly and not infrequently also includes hikayat (saga), which refers to the Gospel of Barnabas or riwayat whose origin cannot be accounted for, his interpretation is also considered too excessive and imposing in relating it to developing science. So that the results of the interpretation are not appropriate or out of the meaning of the verses, and in this context, Al-Qur'an is not an object of research but as evidence and reinforcement of existing scientific findings and as an explanation of the miracles of the Al-Qur'an which was revealed for every age.Penelitian ini membahas kritikan Husein al-Dzahabi tentang dakhil dalam penafsiran Tanthawi Jauhari yang mana dalam penafsirannya, Tanthawi banyak menafsirkan ayat-ayat yang memiliki kaitan dengan ilmu sains (al-ayat al-Kauniyah) yang dikenal dengan tafsir al-‘ilmi. Dengan mengggunkan metode kepustakaan (library research) dan pendekatan deskriptif-kualitatif, penulis memaparkan data yang diperoleh dari kitab al-Tafsir wa al-Mufassirun dan kitab al-Jawahir fi Tafsir Al-Qur’an serta data yang relevan. Maka dapat disimpulkan bahwa dalam penafsirannya, Tanthawi mengambil porsi yang sangat banyak atas penafsiran ayat al-kauniyah (tafsir ilmi) dan ditafsirkan secara singkat dan tidak jarang juga menyertakan hikayat yang merujuk kepada kitab Injil Barnabas atau periwayatan yang tidak dapat dipertanggungjawabkan asal-usulnya, penafsirannya juga dianggap terlalu berlebihan dan memaksakan dalam mengaitkannya dengan ilmu-ilmu sains. Sehingga menjadikan hasil penafsirannya tidak sesuai atau keluar dari maksud ayat-ayat tersebut dan dalam konteks ini Al-Qur'an bukan sebagai objek penelitian tetapi sebagai bukti dan penguat temuan ilmiah yang ada dan sebagai penjelasan tentang keajaiban dan kemukjizatan Al-Qur'an yang diturunkan untuk setiap zaman.